PENGUJIAN MODEL OPSI GARCH UNTUK PENENTUAN HARGA PREMI OPSI SAHAM KETIKA BARRIER DIBERLAKUKAN DI BURSA EFEK INDONESIA - Hendrawan, Riko; Haruman, Tendi (Jurnal Manajemen Teknologi, 2009)
The purpose of this research is to test the accuracy of GARCH Option Model for pricing stock option contract on Astra International, BCA, Indofood and Telkom when barrier is exist at The Indonesia Stock Exchange. Utilizing intraday stock movement and stock option contract data, simulation is conducted using actual data. To test the accuracy of GARCH Option Model, average percentage mean squared error is used to compare simulated premium with its payoff at its maturity date. The finding from this research are one month option average percentage means suared error of GARCH Option Model is three point fifty one percent, two month option is six point sixty one and three month option is seven point sevently nine percent.Katakunci:Â ARIMA, Derivative, Stock Option Contact, Barrier Option, GARCH Option Model, Indonesia Stock Exchange